Otomasi Pemisah Kulit Ari Kacang Kedelai dan Penyaringan pada Pembuatan Susu Kedelai di Desa Kutagandok - Gina Aulia Sari; Naura Mutia Astari; Vita Evelina; Billy Nugraha; Husna Rozaqqiyah (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Stunting in general is a failure condition growth against children, caused by malnutrition in a long time. Milk has a good nutritional content and required by the body for the process of growth. In Indonesia, there are still many toddlers and children who do not consume milk that can cause stunting. It is influenced by the high milk prices in the market. To overcome the problem, soy milk can be a solution, because it contains a substance which is equivalent to cow's milk. The village Kutagandok is one of the villages stunting, which is located in Karawang District. Countermeasures carried out of the village to reduce stunting is the provision of soy milk to toddlers and kids. The process of the production of soy milk is made by the people of the village Kutagandok. But the thing is, there are still some obstacles in the production of, namely the limited human resources (HR) for the separation process soy beans with the skin's epidermis. So then it takes a HR more to make the production time to be shorter. In addition, the length of time filtering soy milk which resulted in easy casserole. The purpose of this service is to help the village of reducing stunting, by way of automation peeler soybeans from the epidermis and the filter tool to separate the soy milk with the dregs. Initially the process of the production of soy milk is used in a conventional manner. Furthermore, through this service uses the peeler semi-conventional. With the filter tool, then the time the production process is faster and quality is better.